Disengagement of Nascent Entrepreneurs from the Start‐Up Process. (20th June 2013) - Khan, Shaji A.; Tang, Jintong; Joshi, Kailash
Abstract : This study examines the roles of entrepreneur motivation and a potentially adverse founding condition in disengagement of nascent entrepreneurs from the start‐up process. Specifically, measures of goal commitment, self‐efficacy, and perceived competition intensity from 943 nascent entrepreneurs are employed to predict disengagement as reported one year later. Results indicate that high perceived competition intensity renders the otherwise strong negative main effect of goal commitment on disengagement, not significant. The even stronger negative main effect of self‐efficacy on disengagement, however, is not contingent on perceived competition intensity. Further, perceived competition intensity by itself does not appear to influence nascent entrepreneurs' disengagement.